Molecular Pathways Involved in Pregnancy-Induced Prevention Against Breast Cancer - Barton, Maria; Santucci-Pereira, Julia; Russo, Jose (Frontiers in Endocrinology, 2014)
Pregnancy produces a protective effect against breast cancer in women who had their first full term pregnancy in their middle twenties. Postponement of the first delivery increases a woman’s breast cancer risk. Also, transiently, during the postpartum period, the risk of developing breast cancer increases. This transient increased risk is taken over by a long lasting protective period. The genomic profile of parous women has shown pregnancy induces a long lasting “genomic signature” that explains the preventive effect on breast cancer. This signature reveals that the differentiation process, conferred by earlier full term pregnancy, is centered in chromatin remodeling. The chromatin remodeling process may be the ultimate step mediating the protection of the breast against developing breast cancer in postmenopausal years.